Is Centralization Needed for Patients Undergoing Distal Pancreatectomy?: A Nationwide Study of 3314 Patients. Issue 9 (October 2019) - Roussel, Edouard; Clément, Guillaume; Lenne, Xavier; Pruvot, François-René; Schwarz, Lilian; Theis, Didier; Truant, Stéphanie; El Amrani, Mehdi
Abstract : Objective: The centralization of complex surgical procedures is associated with better postoperative outcomes. However, little is known about the impact of hospital volume on the outcome after distal pancreatectomy. Methods: Using the French national hospital discharge database, we identified all patients having undergone distal pancreatectomy in France between 2012 and 2015. A spline model was applied to determine the caseload cut-off in annual distal pancreatectomy that influenced 90-day postoperative mortality. Results: A total of 3314 patients were identified. Use of a spline model did not reveal a cut-off in the annual distal pancreatectomy caseload. By taking the median number of distal pancreatectomy (n = 5) and the third quartile (n = 15), we stratified centers into low, intermediate, and high hospital volume groups. The overall postoperative mortality rate was 3.0% and did not differ significantly between these groups. In a multivariable analysis, age, Charlson comorbidity score, septic complications, hemorrhage, shock, and reoperation were independently associated with a greater overall risk of death. However, hospital volume had no impact on mortality after distal pancreatectomy (odds ratio, 0.954; 95% confidence interval, 0.552–1.651, P = 0.867). Conclusions: Hospital volume does not seem to influence mortality after distal pancreatectomy in France, and centralization may not necessarily improve outcomes.